3d phase‐contrast nanotomography of unstained human skin biopsies may identify morphological differences in the dermis and epidermis between subjects. Issue 3 (6th October 2020) - Eckermann, Marina; Peruzzi, Niccolò; Frohn, Jasper; Bech, Martin; Englund, Elisabet; Veress, Béla; Salditt, Tim; Dahlin, Lars B.; Ohlsson, Bodil
Abstract: Background: Enteric neuropathy is described in most patients with gastrointestinal dysmotility and may be found together with reduced intraepidermal nerve fiber density (IENFD). The aim of this pilot study was to assess whether three‐dimensional (3d) imaging of skin biopsies could be used to examine various tissue components in patients with gastrointestinal dysmotility. Material and methods: Four dysmotility patients of different etiology and two healthy volunteers were included. From each subject, two 3‐mm punch skin biopsies were stained with antibodies against protein gene product 9.5 or evaluated as a whole with two X‐ray phase‐contrast computed tomography (CT) setups, a laboratory µCT setup and a dedicated synchrotron radiation nanoCT end‐station. Results: Two patients had reduced IENFD, and two normal IENFD, compared with controls. µCT and X‐ray phase‐contrast holographic nanotomography scanned whole tissue specimens, with optional high‐resolution scans revealing delicate structures, without differentiation of various fibers and cells. Irregular architecture of dermal fibers was observed in the patient with Ehlers‐Danlos syndrome and the patient with idiopathic dysmotility showed an abundance of mesenchymal ground substance. Conclusions: 3d phase‐contrast tomographic imaging may be useful to illustrate traits of connective tissue dysfunction in various organs and to demonstrate whether disorganized dermal fibers could explain organ dysfunction.